READ ALOUD METHOD TO IMPROVE THE READING SKILLS OF MI AL-ISLAM PRAMPELAN STUDENTS - Masrur Afandi (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
Reading is an activity used to increase knowledge and experience to increase intelligence. Lack of reading skills makes students find it difficult to understand the content of the writing they read. Based on the background, the aim of the read aloud learning program carried out by the author is to improve students' reading skills, so that they can more easily understand and capture the results well from the writing they read. In implementing this service activity, the ABCD (Asset Based Community Development) approach is used. This community service program was carried out in class 3 at MI Al-Islam Prampelan, Adipuro, Kaliangkrik, Magelang, using picture story media through digital books. The result of this service activity is that through the read aloud learning program using picture story media, students' ability to use punctuation, intonation, and comprehension ability in reading and understanding improves.